Система автоматизованого контролю функціонального стану людини, що перебуває у ергатичній системі «особа-комп’ютер» - Страхова, Оксана Петрівна; Strakhova, O. P. (Запорізький державний медичний університет, 2019)
Дисертаційна робота присвячена вирішенню завдання створення автоматизованої системи контролю функціонального стану осіб, які навчаються в комп’ютерному ергатичному навчальному середовищі, за допомогою інтегрального критерію – електрошкірних характеристик мікрозон. На основі відкритого в ході виконання наукового дослідження й уперше описаного явища стабільності середніх значень електрошкірних параметрів мікрозон обґрунтовано сутність інтегрального критерію оцінювання відносних змін функціональних станів людини в ергатичному комп’ютерному середовищі. Запропоновано новий метод обробки показників електрошкірних характеристик і побудови на їх основі висновків щодо змін функціонального стану людини. Доведено, що цей новий метод має високу кореляцію з параметрами функціонального стану людини, отриманими добре відомими й широко вживаними способами його визначення. Створено структурну схему і систему дистанційного контролю стану людини, яка працює в комп’ютерному середовищі, з метою своєчасного коригування негативного впливу на стан здоров’я студента за допомогою технологій Bluetooth та Wi-Fi. The dissertation is devoted to the development of the system of automated control of the functional state of the person working in the ergatic computer system, on the basis of the proposed method of monitoring the changes in the status of the person being trained in the «person – computer» system. In the research process, verifying the existence of correlations between a person‘s functional state parameters determined by the heart rate variability and rheovasography, and the skin electrical parameters of the microzones on the person’s body, was carried out. The phenomenon of the electro conductivity stability at the control points on the human body was first opened and described and Copyright certificate No. 56102, August 18, 2014 was received. The phenomenon consists in the stability of the calculated averages of skin electrical parameters in the control microzones. Averages calculations were provided in accordance with the method proposed by the author, separately for the accumulated array of measurements of each microzone, by the rule of processing homogeneous data, which makes it possible to determine the permissible limits of changes in the parameters of the electroskin parameters of each control microzone separately. The main scientific results of the study are the next. For the first time a model of the automated control system for the person’s functional state in an ergatic computer environment based on the electroskin parameters control in the microzones, is proposed. The phenomenon of the average electro conductivity stability at the control points on the human body was discovered and described for the first time. An integral criterion for changing the functional state of individuals in ergatic systems was developed, based on the parameters of the skin electrical parameters of the control microzone. A new method for defining the functional state of person’ working in the ergatic system was created on the basis of the integral criterion developed in accordance with the author’s first described phenomenon of stability of the mean values of the parameters of the skin electrical parameters in the control microzone.
The automated control system of a person’s functional state in ergatic system "person-computer"
Keywords: ергатична навчальна система; функціональний стан; електрошкірні характеристики; варіабельність серцевого ритму; реовазографія; ситуативна та особистісна тривожність; Bluetooth; Wi-Fi; ergatic educational system; functional status; electroskin characteristics; heart rate variability; rheovasography; situational and personal anxiety; control system